2014
DOI: 10.1111/jcpe.12329
|View full text |Cite
|
Sign up to set email alerts
|

Pre‐clinical evaluation of the osteogenic potential of bone morphogenetic protein‐2 loaded onto a particulate porcine bone biomaterial

Abstract: Bone morphogenetic protein-2 enhanced local bone formation in the rabbit maxillary sinus model following implantation using a PBM carrier.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
21
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 21 publications
(25 citation statements)
references
References 27 publications
3
21
1
Order By: Relevance
“…The results of this study showed lower values of total augmented area than previous studies that have investigated the effect of BMP-2 in the same experimental model [15911]. The smaller total augmented area could be associated with characteristics of the grafted material.…”
Section: Discussioncontrasting
confidence: 61%
See 2 more Smart Citations
“…The results of this study showed lower values of total augmented area than previous studies that have investigated the effect of BMP-2 in the same experimental model [15911]. The smaller total augmented area could be associated with characteristics of the grafted material.…”
Section: Discussioncontrasting
confidence: 61%
“…Therefore, studies with a lower dose in the range 0.10–0.15 mg/mL of BMP-2 have been conducted in rabbit sinuses with various healing periods. In another previous study with 0.1 mg/mL of BMP-2, new bone formation of the BMP group was statistically greater than that of the control group [11]. Kim et al [1] reported similar data with the same concentration of BMP-2 in a previous study and the area of newly formed bone of the BMP group was significantly greater than that of the control group at weeks 2 and 4 of the healing period.…”
Section: Discussionmentioning
confidence: 64%
See 1 more Smart Citation
“…(). Although several animal platforms including rabbit (Yon et al., ), dog (Schlegel, Fichtner, Schultze‐Mosgau, & Wiltfang, ), mini‐pig (Terheyden et al., ), goat/sheep (Philipp et al., ), and nonhuman primates (Hanisch et al., ) have been employed to evaluate sinus augmentation protocols, the mini‐pig model presents several advantages (Lee, Fiorini, Wikesjö, & Susin, ). Due to the convenient size and disposition of the maxillary sinus, the mini‐pig features skeletal proportions that allow the use of dental implants of clinically meaningful dimensions.…”
Section: Discussionmentioning
confidence: 99%
“…The introduction of recombinant human bone morphogenetic protein-2 (rhBMP-2) was considered revolutionary in both fulfilling clinical needs and overcoming shortcomings of traditional procedures. Numerous preclinical studies have found that the use of rhBMP-2 induced exceptional bone regeneration within a short healing period [26]. Unfortunately, the use of rhBMP-2 is restricted to few indications (only maxillary sinus augmentation and extraction socket), due to its relatively high cost and potential complications such as extensive postoperative swelling and seroma formation [7, 8].…”
Section: Introductionmentioning
confidence: 99%